Bacterial profile of surfaces and equipment in the Intensive Care Unit of a University Hospital (Research, Society and Development, 2021)
There is evidence that surfaces and objects act as reservoirs, thus facilitating cross-infections. The objective of the present work was to evaluate the bacterial profile on surfaces and equipment of the ICU of the University Hospital of the Federal University of Vale do São Francisco. This is a cross-sectional and descriptive study. The study was carried out in the ICU, where the following surfaces and equipment were sampled: mechanical ventilator; cardiac monitor command buttons; stethoscope diaphragm; bedside table; serum/food dispenser; curtains around the bed; wall around the bed and continuous infusion pump. Samples were collected using swabs soaked in saline solution. After passage, they were stored in a tube and transported to the Laboratory where microbiological analyzes were performed. The total bacteria found, regardless of the beds, equipment and surfaces sampled was 134, of these, 20 (15%) are considered possible bacteria that cause hospital infections. Regarding the resistance profile of bacteria to the main antibiotics, Staphylococcus aureus were 100% oxacillin resistant and Enterococcus sp. presented 20% intermediate resistance to vancomycin and 20% resistance to ampicillin. All isolates of Klebsiella pneumoniae were found to be ampicillin + sulbactam resistant and 100% sensitive to the remaining antibiotics tested. Acinetobacter baumannii showed 43% intermediate resistance to ceftriaxone and 57% meropenem resistance. The present study shows that on the ICU surfaces and equipment there are multiresistant bacteria that can cause nosocomial infections.